The Job Loss Insurance Program as a Government Policy Response to Address the Impact of National Economic Fluctuations and Layoffs - Putri, Indah Anggoro; Nasution, Faizal Amir P; Muhyiddin, Muhyiddin (Pusat Pengembangan Kebijakan Ketenagakerjaan Kementerian Ketenagakerjaan Republik Indonesia, 2024)
Fluctuations in the national economy caused by several things, such as a decline in economic growth, the global economic crisis, and the COVID-19 pandemic, often lead to layoffs (PHK). Layoffs have various negative impacts on life, such as depression, mental health, financial problems, social relationships, decreased physical health, and impacts on careers. The JKP program is one of the policies to overcome these negative impacts. The JKP program is designed to provide financial support, job training, and access to labor market information for laid-off workers, with the aim of reducing the social and economic impact of layoffs and helping workers return to the labor market with better skills. The aim of this research is to explain the JKP program as a response to government policy in overcoming the negative impacts of layoffs. This research uses a qualitative and quantitative descriptive approach. The implementation of the JKP program has shown positive results, such as increasing people's purchasing power and contributing to economic recovery. However, there are several challenges in its implementation, including infrastructure, technical problems and uneven socialization. Periodic program evaluation is needed to address this problem and ensure the long-term effectiveness of the JKP program. This article also emphasizes the importance of collaboration between government and industry in improving the relevance and quality of vocational training. It is hoped that the JKP program can continue to adapt and improve protection for workers in Indonesia, thereby providing better economic and social stability